Advances in Mineral Nutrition Transport and Signal Transduction in Rosaceae Fruit Quality and Postharvest Storage - Bai, Qian; Shen, Yuanyue; Huang, Yun (Frontiers in Plant Science, 2021)
Plant mineral nutrition taken up from the soil plays fundamental roles in plant growth and development. Among of at least 14 mineral elements, the macronutrients potassium (K), phosphorus (P), nitrogen (N), calcium (Ca), and the micronutrients iron (Fe) are essential to crop yield and quality. Deficiencies in minerals strongly affect metabolism with subsequent impacts on the growth and development of fruit trees. This will ultimately affect the yield, nutritional value, and quality of fruit. In addition, the main reason of the postharvest storage loss caused by physiological disorders is the improper proportion of mineral nutrients elements. In recent years, much progress has been made in understanding the molecular mechanisms for mineral nutrition (N, P, K, Ca, Fe) in various aspects of plant growth, fruit development, quality, nutrition and preservation, especially highlighting N in fruit yield, P and K in fruit quality. Mineral nutrition like N, P and Fe not only affects fruit quality independently but also affects the absorption of other nutrient elements. In this review, we provide insights into the transport, signal and the fruit quality regulation of these mineral nutrients at physiological and molecular levels. These studies will contribute to provide theoretical basis to improve fertilizer efficient utilization and fruit quality formation.